Sarapatel caprino: valor nutricional e qualidade microbiológica - Brasil, Luciana Medeiros da Silva (2014)
Goat sarapatel is produced using goat blood and viscera. It represents an economical alternative to the use of the by goat slaughter. This product, typical of northeastern Brazil, presents no standardization in its formulation, which can lead to a wide variation in its composition and nutritional quality. The objective of this research was, therefore, to evaluate the microbiological and nutritional of the quality goat sarapatel which is commercialized at different places points and under different storage conditions in the city of João Pessoa, Paraíba, Brazil. For this experiment work, a total of 48 samples of goat sarapatel were analyzed; there were obtained from a variety of places, such as street fairs, butcher shops and supermarkets. As a result of being acquired from different places the condition of each samples varied: some were frozen, others were refrigerated and there were a few under room temperature. The physico-chemical quality of goat sarapatel presented an remarkable nutritional value (each 100g of goat sarapatel presented, on average, 72g of moisture, 2g of ash, 18g of protein, 9g of fat and 2g of carbs).Its fatty acid profile showed a high amount of unsaturated fatty acids, especially oleic, linoleic and linolenic acids. In the amino acid profile analysis, 18 amino acids were identified, especially the amino acids lysine, histidine, leucine, phenylalanine and valine. There amino acids are considered essential, which makes the sarapatel a protein source with a high nutritional value. The samples also presented a high level of cholesterol, with an average concentration of 282mg/100g. The results of the microbiological analyses of the samples revealed the absence of Salmonella spp. and L monocytogenes. However, high levels of total coliform, thermotolerant and Clostridium sulphite reducer were found, ranging from 1,5x104 to >1,1x105 NMP/g; from 2,4x104 to >1,1x105 NMP/g; and from 3,2x103 to 9,8x105 UFC/g, respectively. Positive Staphylococcus coagulase was present in 31.25% of the samples, with level counts ranging from 4,3x104 to 1,2x105 UFC/g. These results show that the samples of goat sarapatel sold in the city of João Pessoa/PB present acceptable nutritional value; however, their microbiological quality is unsatisfactory, which may represent a risk to consumer health. The involvement of regulatory agencies in the production process is therefore necessary, in order to promote health and safety measures and make sure this products is safe for consumption.